Poul Andersen (1888-1977) – The Son of a Tenant Farmer - Blomquist, Helle (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2025)
In August 1910, a young man arrived at Copenhagen Central Station. All day he had traveled from his parent’s farm on Funen all day, and now he was ready to go to his lodgings. He had enrolled in the Law Faculty of Copenhagen University and acquired a room at a desired dormitory, Valkendorf Kollegium, next door to the auditoriums. His name was Poul Andersen, later to become the law professor that founded Danish administrative law. I view his life and background, his work in public law, and the development of the Danish political transition. In this, I claim to illustrate how, at the beginning of the 20th century, he took it upon himself to transform Danish public law to serve a democratic society. In doing so, his profound inspiration was the great democratic politician and thinker Frederik Severin Grundtvig. It brings to light the function of the lawyer, not as a neutral technician but as an agent of societal change.